Comparative Haematological and Serum Biochemical Evaluation of Rats Fed with Hydro-ethanolic Leaves Extracts of Moringa oleifera and Telfairia occidentalis - E.F., Udo; O.I., Olantunji; F.T., Abayomi; A.M., Idowu; A.O., Abiodun (Covenant Journal of Physical and Life Sciences, 2017)
The study was carried out to compare the effect of hydro-ethanolic leaves extract (MOLHE) and (TOLHE) of Moringa oleifera and Telfairia Occidentalis respectively on some haematogical and serum biochemical indices. A total of fifty wistar rats of both sexes (110-255g) were randomly allotted into five groups: A to E (n = 5). Group A (control) received water treatment equivalence.Â Groups B and D; C and E received 200mg/kg and 300mg/kg of TOHLE; MOLHE orally for 7 and 14 days respectively. Animals in group B and D significantly increased packed cell volume (PCV), Haemoglobin (Hb) and neutrophil levels. Group C had no significant effect on haematological indices while group E treated with 300mg/kg MOLHE showed dose dependent significant increases in PCV, Hb and lymphocyte levels in comparison with the control. Animals of both extracts recorded insignificant changes in white blood cells (WBC) compared to control. Animals in groups B and C significantly (p<0.05) showed increased total protein concentration at 200mg/kg while serum total cholesterol (TC) was